Inovasi Pengolahan Limbah Cair dari Pusat Perbelanjaan Kota Malang dengan Metode Aerasi - Susanto, Susanto; Khalimatus Sa'diyah; Wianthi Septia Witasari; Febby Anisa Putri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
One of the problems posed by shopping centers is liquid waste. This community service activity aims to find alternative solutions for liquid waste treatment in shopping centers. Based on the shopping centers problem, the community service team of State Polytechnic of Malang tried to offer a solution to the problem through the treatment of liquid waste from one of the shopping centers in Malang using aerobic waste treatment with a modified aeration method with Bioball adhesive media. Based on the results of wastewater treatment by aeration, it was obtained that the domestic wastewater of shopping centers treated by the aeration method has a COD content of 3,570 mg/L, BOD5 content of 1,136 mg/L, TSS content of 233 mg/L, and pH of 6.15. The results meet the quality standards of domestic wastewater for pH but have not met the quality standards of COD, BOD5, and TSS. COD parameters can decrease effectively when compared with the results of biofilter waste treatment. The operator of the liquid waste management of the shopping center is also quite satisfied with the result. It is necessary to develop further innovations to reduce TSS, BOD5, and COD levels in domestic wastewater in shopping centers, such as combining absorption methods and aeration methods in order to obtain results that can meet domestic wastewater quality standards.